SURVIVING AGAINST CELEBRITY YOUTUBERS: AN ANALYSIS OF RAHMAWATI KEKEYI PUTRI CANTIKA - Lambok Hermanto Sihombing; Aulia Kemala Dewi; Fadillah Nuraini (Metacommunication: Journal of Communication Studies, 2021)
The phenomenon of many people that want to become YouTubers has become trending segments nowadays. Most of people that try to become YouTubers try to reach people attention in order to get their own popularity. YouTubers compete among others to create interesting or even controversial content. One of them can be seen from a YouTuber named Rahmawati Kekeyi Putri Cantika. The aims of this study is to  find out the communication strategy applied by Kekeyi on her YouTube account as she did it as the way to maintain and increase her popularity. The data of this research was obtained from one of the controversial contents uploaded by Kekeyi on her YouTube account. This study used impression management theory as the grand theory, and two supporting theories; self-representational behavior theory and dramaturgy theory.Using the three theories above, researchers selected Kekeyi's content in the form of video as an analytical material. The researchers discovered that Kekeyi applied aspects of the three theories above on her YouTube content as the strategy to maintain and increase her popularity on YouTube.